A new species of Neidiomorpha (Bacillariophyceae) from Dianshan Lake in Shanghai, China - Luo, Fen; Yang, Qi; Guo, Kaijuan; Liu, Tengteng; Wang, Quanxi; You, Qingmin (Phytotaxa, 2019)
A new diatom species, Neidiomorpha dianshaniana sp. nov., found in Dianshan Lake in Shanghai, China, is described herein. The morphology of N. dianshaniana has been documented by light and scanning electron microscopy. Neidiomorpha dianshaniana valves are elliptical in outline with rostrate apices. Raphe is almost straight and filiform. The axial area is narrow and linear. The central area is small, round to transversely elliptical or irregular. Striae are slightly radiate and almost parallel near the apices. Puncta are arranged in undulating longitudinal rows. Neidiomorpha dianshaniana’s most visible feature is its lack of central constriction, in which respect it differs from the three other species in the genus Neidiomorpha.